Pengaruh Konformitas terhadap Prokrastinasi Akademik Mahasiswa di Universitas Negeri Makassar - Azzahra, Raodahtun Qori; Alwi, M. Ahkam (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The problem of procrastination in students is a phenomenon that occurs which can have a negative impact on students. One of the negative impacts that occurs when procrastinating is not being able to submit assignments on time. Most students postpone assignments due to various factors. One of the factors that influences students' academic procrastination behavior is conformity. This research aims to see the effect of conformity on academic procrastination among Makassar State University students. The sampling technique uses accidental sampling technique. This research used quantitative methods with research respondents totaling 381 active students at Makassar State University. The results of the research show that there is a significant influence between conformity and academic procrastination among students (b = 0.572, p = 0.00 < 0.05), indicating that the higher the conformity score, the higher the academic procrastination among Makassar State University students. It is hoped that this research can serve as a guide for developing students' skills in overcoming academic procrastination behavior, so that students can complete their lecture assignments on time.